Relapsed/refractory diffuse large B-cell lymphoma patients. A multicenter retrospective analysis of eligibility criteria for car-T cell therapy. Issue 4 (21st March 2021) - Di Rocco, Alice; Cuneo, Antonio; Di Rocco, Arianna; Merli, Francesco; De Luca, Giulia; Petrucci, Luigi; Ansuinelli, Michela; Penna, Domenico; Rotondo, Francesco; Rigolin, Gian Matteo; Giaimo, Mariateresa; Re, Francesca; et al.
Abstract: Anti-CD19 chimeric antigen receptor (CAR) T cells represent the first approved third-line therapy associated with long-term remissions in patients with refractory/relapsed (R/R) diffuse large B-cell lymphoma (DLBCL). Eligibility criteria to identify patients who can successfully receive CAR-T are still debated. For this reason, the aim of this study was to identify factors influencing eligibility and define a realistic patient estimate. Of 1100 DLBCL patients, 137 were included. Based on the Juliet trial inclusion criteria, only 64 patients (46.7%) would be eligible. Median overall survival (OS) was 8.04 months in eligible vs 3.23 in non-eligible patients ( p < 0.001). Multivariate analysis identified stage III-IV ( p = 0.017) and ECOG ≥ 2 ( p < 0.001) as significant independent prognostic factors for OS. Moreover, only 64/1100 (5.8%) DLBCL patients would be truly eligible for CAR-T. Our real-life data confirm that with a longer waiting time patients with advanced stage and poor ECOG are less likely to be eligible for CAR-T cell infusion.